The relationship between motivation and work compensation with nurse performance - Wardani, Diah Sukma; Siregar, Santy Deasy; Siagian, Masryna (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
This study investigates the relationship between motivation, compensation, and nurse performance at Muyang Kute Hospital, Bener Meriah Regency, Indonesia, using an analytical survey with a cross-sectional design. A sample of 154 nurses was randomly selected from a population of 250. Data were collected via questionnaires measuring motivation, compensation, and performance, categorized as